2009
DOI: 10.1097/fpc.0b013e3283163ecd
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing of serotonin-related genes and association of tagging SNPs to citalopram response

Abstract: Several reports have been published investigating the relationship between common variants in serotonin-related candidate genes and antidepressant response, and most of the results have been equivocal. We previously reported a significant association between variants in serotonin-related genes and response to the selective serotonin reuptake inhibitor fluoxetine. Here, we attempt to expand upon and replicate these results by (i) resequencing the exonic and putatively regulatory regions of five serotonin-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 33 publications
4
37
1
5
Order By: Relevance
“…McMahon et al (2006) reported an association between rs7997012 and rs1928040 in HTR2A and the outcome of citalopram treatment in a very large sample of outpatients with MDD. Peters et al (2009) replicated those findings in a study showing that rs7997012 was associated with citalopram response in MDD. However, Perlis et al (2009) reported that rs7997012 and rs1928040 were not associated with duloxetine treatment outcome in MDD.…”
Section: Introductionsupporting
confidence: 81%
“…McMahon et al (2006) reported an association between rs7997012 and rs1928040 in HTR2A and the outcome of citalopram treatment in a very large sample of outpatients with MDD. Peters et al (2009) replicated those findings in a study showing that rs7997012 was associated with citalopram response in MDD. However, Perlis et al (2009) reported that rs7997012 and rs1928040 were not associated with duloxetine treatment outcome in MDD.…”
Section: Introductionsupporting
confidence: 81%
“…However, whereas some studies show a significant link between a TPH2 SNP haplotype and specific responses to 5-HT reuptake inhibitors (SSRIs) [49,94,95], others, here again, do not confirm any association between this trait and TPH2 SNPs in various ethnic groups [60,62,72] .…”
Section: Peripheral Effectsmentioning
confidence: 48%
“…The fact that the mutation is located within the part of the oligomerization domain that has previously been shown to be pivotal for TPH 2 activity [63] together with the description of a corresponding severe pathogenic mutation in PAH (R408W) led to the expectation that the first lossof-function mutation in human TPH2 had been identified [64] . However, this functional polymorphism could not be confirmed in any other study [62,[65][66][67][68][69][70][71][72] . Thus it is either a rare mutation within a very unique cohort with unipolar depression or the result of a genotyping error.…”
Section: Genetic Studies On Tph In Humansmentioning
confidence: 74%
“…259 Several other variants have been reported to predict antidepressant response. 85,117,134,179,229,260,261 Table 8 lists relevant genetic association studies that investigated the impact of these variations on the antidepressant response.…”
Section: Serotonin 2amentioning
confidence: 99%